Gender differences in long‐term outcome after primary percutaneous intervention for ST‐segment elevation myocardial infarction. Issue 3 (29th April 2013) - Wijnbergen, Inge; Tijssen, Jan; van 't, Marcel; Michels, Rolf; Pijls, Nico H.J.
<x xml:space="preserve">Abstract</x> Background Previous studies on gender differences in outcome in patients with ST segment elevation myocardial infarction (STEMI) have been performed, but most of those are from before the current era of PCI technique and medical therapy and have a short duration of follow‐up. The objective of our study is to assess the influence of gender on long‐term outcome in patients with STEMI who underwent primary percutaneous intervention (PCI) between January 2006 and May 2008. Methods Two‐year follow‐up data from 202 female and 668 male patients undergoing primary PCI for STEMI were available from the DEBATER (A Comparison of Drug Eluting and Bare Metal Stents for Primary Percutaneous Coronary Intervention with or without Abciximab in ST‐segment elevation Myocardial Infarction: The Eindhoven Reperfusion Study) trial database. The primary endpoint was major adverse cardiac events (MACE), defined as the composite of death, myocardial infarction, and target vessel revascularization. Results Women were older (64.7 ± 11.7 vs. 59.0 ± 10.7; P < 0.001), and had more often diabetes mellitus (15% vs. 9%; P = 0.01) and hypertension (44% vs. 25%; P < 0.001). At two years, the rate of MACE was significantly higher in women (21% vs. 14%; P = 0.02). The mortality rate in women was 8% versus 2.6% in men (P < 0.001). However, multivariate analysis after adjustment for age and the baseline characteristics hypertension, smoking, diabetes mellitus, stent diameter, and time between onset of symptoms and arrival of the ambulance showed similar MACE and mortality rates in men and women. Conclusion Women have higher rates of both MACE and mortality after primary PCI for STEMI compared to men because of higher age with higher baseline risk profiles.© 2013 Wiley Periodicals, Inc.